External Iliac Artery Injury and Thrombosis during Laparoscopic Gynecologic Surgery - Masako Ishikawa; Kentaro Nakayama; Sultana Razia; Hitomi Yamashita; Tomoka Ishibashi; Seiya Sato; Hiroki Sasamori; Kiyoka Sawada; Sonomi Kurose; Noriyoshi Ishikawa; Shoichi Suehiro; Satoru Kyo (Case Reports in Obstetrics and Gynecology)
Although vascular injury during laparoscopic surgery is rare, it is occasionally reported. Previously, several physicians have reported cases of compartment syndrome resulting from a thrombus during gynecologic surgery. However, few reports describe thrombosis occurring in artery vessels as a result of applying angiopressure. Herein, we report the case of a 53-year-old woman with endometrioid carcinoma and a vascular injury that resulted in thrombus formation; this is the first such case to be reported. The complication was successfully treated by means of direct anastomosis following partial resection of the injured iliac artery. This is the first report of a case in which applying angiopressure for a vascular injury during laparoscopic pelvic lymphadenectomy led to an intra-arterial thrombus which was found and treated without sequelae.